2020
DOI: 10.1563/aaid-joi-d-19-00274
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health–Related Quality of Life and Full-Arch Immediate Loading Rehabilitation: An Evaluation of Preoperative, Intermediate, and Posttreatment Assessments of Patients Using a Modification of the OHIP Questionnaire

Abstract: The aim of this study was to assess oral health related quality of life (OHRQoL) of patients before, during and after completion of implant-supported full-arch immediate loading rehabilitation according to the Columbus Bridge Protocol (CBP). 25 patients with compromised dentition were rehabilitated according to the CBP and were assessed for OHRQoL using 4 questionnaires specifically realized for this study and inspired to the OHIP (Oral Health Impact Profile) questionnaire. Patients assessed themselves before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 22 publications
(27 reference statements)
1
19
0
Order By: Relevance
“…At the final evaluation, 4 months after rehabilitation, 92% of patients did not indicate any difficulty in eating. Overall, oral health‐related quality of life revealed a significant improvement in terms of quality of life, and the patients only reported phonetic impairment in the immediate aftermath of surgery 44 . Two prospective studies indicated that implant‐supported prostheses improved the oral health‐related quality of life significantly 45,46 .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…At the final evaluation, 4 months after rehabilitation, 92% of patients did not indicate any difficulty in eating. Overall, oral health‐related quality of life revealed a significant improvement in terms of quality of life, and the patients only reported phonetic impairment in the immediate aftermath of surgery 44 . Two prospective studies indicated that implant‐supported prostheses improved the oral health‐related quality of life significantly 45,46 .…”
Section: Resultsmentioning
confidence: 98%
“…42 Fonteyne et al 43 treatment, patients were very satisfied with their oral health-related quality of life and their speech. 43 Similarly, Dellepiane et al 44 and the patients only reported phonetic impairment in the immediate aftermath of surgery. 44 Two prospective studies indicated that implant-supported prostheses improved the oral health-related quality of life significantly.…”
Section: Fully Edentulous Patientsmentioning
confidence: 91%
See 1 more Smart Citation
“…The OHIP-EDENT is a commonly utilized tool, considered principally described and demonstrated good reliability and validity. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…However, the OHIP is the most frequently used instrument and remains the best documented [ 34 ]. In addition to the influence of prosthetic rehabilitations on patients’ quality of life, it is also important to determine their level of satisfaction/dissatisfaction [ 35 , 36 ].…”
Section: Introductionmentioning
confidence: 99%